2004
DOI: 10.1007/s00251-004-0721-y
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive evidence of association of C-159T functional polymorphism of the CD14 gene with atopic asthma in northern and northwestern Indian populations

Abstract: CD14 is a lipopolysaccharide receptor known to be an important modulator of Th1-Th2 response during early childhood. Genetic association studies of the CD14 gene with asthma and atopic disorders have shown positive as well as negative results in different ethnic populations. The aim of this study was to test for association of C-159T functional promoter polymorphism with atopic asthma and serum IgE levels in northern and northwestern Indian populations. DNA was assayed for the CD14 C-159T polymorphism in a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
3
22
2
Order By: Relevance
“…The authors also performed a meta-analysis of 12 previous studies from different populations and confirmed no association with asthma or atopy, although there was significant heterogeneity between studies [39 ]. In contrast, a study of 187 atopic asthmatics, 227 controls and 106 trios in India found that the -159T allele was associated with reduced risk of asthma, and (in the case-control study) reduced total serum IgE [40 ].…”
Section: Cd14 In Adult Asthma and Atopymentioning
confidence: 82%
“…The authors also performed a meta-analysis of 12 previous studies from different populations and confirmed no association with asthma or atopy, although there was significant heterogeneity between studies [39 ]. In contrast, a study of 187 atopic asthmatics, 227 controls and 106 trios in India found that the -159T allele was associated with reduced risk of asthma, and (in the case-control study) reduced total serum IgE [40 ].…”
Section: Cd14 In Adult Asthma and Atopymentioning
confidence: 82%
“…[5][6][7][8][9][10] Significant associations have also been observed between this Abbreviations used AOAH: Acyloxyacyl hydroxylase FBAT: Family-based association test LD: Linkage disequilibrium OR: Odds ratio sCD14: Soluble CD14 SNP: Single nucleotide polymorphism tIgE: Total IgE marker and asthma. [11][12][13] LeVan et al 14 showed this polymorphism is functional, resulting in higher soluble CD14 (sCD14) concentrations. To date, the CD14(2260)C>T polymorphism is one of the most reproducible associations for asthma and its associated traits.…”
mentioning
confidence: 99%
“…In view of the absence of the CD14 polymorphism in the sample studied, it was not possible to estimate population genetic parameters as proposed in the section Material and Methods. In humans, the C159T SNP of the CD14 gene has been associated with asthma and IgE levels in populations from northern and northwestern India (Sharma et al, 2004). Recently, Faria et al (2009) investigated the association of this polymorphism with the severity of lung disease in cystic fibrosis.…”
Section: Resultsmentioning
confidence: 99%